Mesoscopic Fracture Model of Coarse Aggregate Interlocking Concrete - Ben Li; Ying Yu; Chen Zhang; Yu Zhang (Advances in Materials Science and Engineering)
The skeleton formed by coarse aggregate has an important influence on the macroscopic mechanical properties of concrete, especially the fracture properties. Based on mesomechanics and fracture mechanics, this paper conducts theoretical simulations and experimental studies on the mechanical and fracture properties of coarse aggregate interlocking concrete through the theory of mesomechanics homogenization as well as compressive strength tests, flexural strength tests, axial compressive strength tests, elastic modulus tests, and fracture toughness tests. The results show that when the coarse aggregate is within a certain volume increase, the fracture energy and ultimate strength of concrete are significantly improved. At the same time, the proposed mesomechanics calculation model has high accuracy for calculating the fracture characteristics of concrete when the coarse aggregate increment is less than 20%.